DETERMINANTS OF CO₂ EMISSIONS: EMPIRICAL EVIDENCE FROM INDONESIA - Septiani, Yustirania; Sartika, Rebecca Cindy; Oktaviani, Vennesa Bagus (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
Economic growth in developing countries is often accompanied by an increase in carbon dioxide (CO₂) emissions. Indonesia, as one of the largest economies in Southeast Asia, deals with a dilemma between driving for Gross Domestic Product (GDP) growth, open trade, and high dependence on fossil energy, all of which lead to serious impacts on environmental quality. This study aims to analyze the effect of GDP, open trade, and fossil energy consumption on Indonesia’s CO₂ emissions in the period 1994–2024 using 31 annual observations. The dataset is primarily obtained from the World Bank’s. The research applies descriptive method with OLS regression. The results indicate that GDP, open trade, and fossil energy consumption have a positive and significant impact on CO₂ emissions. GDP growth drives higher emissions through industrial and economic activities that are not yet fully aligned with environmentally friendly principles. Fossil energy consumption is proven to be the main driver of emissions, while open trade also contributes to rising emissions through the scale effect of economic activities.